1989
DOI: 10.1007/bf00378660
|View full text |Cite
|
Sign up to set email alerts
|

Host specificity among Maculinea butterflies in Myrmica ant nests

Abstract: Ecological studies have been made of all 5 European species of Maculinea. These confirm that M. nausithous and M. rebeli live underground in Myrmica ant nests for 10 months of the year, as has long been known for the other 3 species. The main discovery was that each Maculinea species depends on a single, and different, host species of Myrmica. This specificity contradicts previous papers and scientific reviews of the relationship between Maculinea and ants. Therefore, early records are re-examined and 3 reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
184
2
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 191 publications
(188 citation statements)
references
References 13 publications
0
184
2
2
Order By: Relevance
“…It was shown that M. scabrinodis was the most abundant Myrmica species in the metapopulation system in the Kraków region but the percentage of infested nests was similar or even lower than those of nests of M. rubra or M. ruginodis. Moreover, a decrease of infested nests of M. scabrinodis has been observed during the last 20 years (Thomas et al, 1989;Witek et al, 2010). This trend could be the consequence of the arms-race between the parasite and its host, which was also observed in other interactions between social parasites and their hosts (Lorenzi and Filippone, 2000;Foitzik et al, 2003;.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…It was shown that M. scabrinodis was the most abundant Myrmica species in the metapopulation system in the Kraków region but the percentage of infested nests was similar or even lower than those of nests of M. rubra or M. ruginodis. Moreover, a decrease of infested nests of M. scabrinodis has been observed during the last 20 years (Thomas et al, 1989;Witek et al, 2010). This trend could be the consequence of the arms-race between the parasite and its host, which was also observed in other interactions between social parasites and their hosts (Lorenzi and Filippone, 2000;Foitzik et al, 2003;.…”
Section: Discussionmentioning
confidence: 92%
“…Some Myrmica hosts, such as M. rugulosa, adopt larvae very quickly and readily but then the survival of the butterfly larvae is relatively low, whereas colonies of M. ruginodis had lower rates of adoption of M. teleius larvae, but later survival and increase in body mass for larvae was high. Additionally, it was not possible to show that M. scabrinodis, which was considered as the main host of M. teleius (Thomas et al, 1989), provided the best conditions for adoption and development of M. teleius larvae. Therefore, we have to conclude that some Myrmica species are better hosts during adoption and initial integration phases while others provide better conditions for the later development of M. teleius larvae.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations